RHSS 2022
DOI: 10.7176/rhss/12-4-01
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into using Nearpod as an Interactive Tool to Aid Students’ Achievement and Motivation for Learning Educational Technology

Abstract: SQU) has been using various interactive applications, such as Padlet, Nearpod, Wordwall, etc. The department has adopted and adapted its courses and teaching strategies to take better advantage of these advanced technologies in the teaching and assessment process. In this study, we selected Nearpod as an interactive tool for teaching an introductory course on Educational Technology (TECH3007). Nearpod is a web-based application that enhances students' motivation with interactive content and serves as an excell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…One definition of active learning is any learning approach that allows students to do an active learning task and encourages them to think about the activities they are involving themselves in. Active learning can be defined as any learning approach that allows students to do an active learning task (Mohamed & Corresponding, 2022). To put it another way, the student gets experience in working, communicating, and receiving during the course of the class, which can be utilized to distinguish active learning from passive learning (Naumoska et al, 2022).…”
Section: A Introductionmentioning
confidence: 99%
“…One definition of active learning is any learning approach that allows students to do an active learning task and encourages them to think about the activities they are involving themselves in. Active learning can be defined as any learning approach that allows students to do an active learning task (Mohamed & Corresponding, 2022). To put it another way, the student gets experience in working, communicating, and receiving during the course of the class, which can be utilized to distinguish active learning from passive learning (Naumoska et al, 2022).…”
Section: A Introductionmentioning
confidence: 99%
“…The use of Nearpod in the learning process shows increased understanding because active and collaborative learning can occur (Rios-Zaruma et al, 2019). Furthermore, the use of the collaborative aspects during face-to-face and online learning provides opportunities for students to interact with content, activities, teachers, and other students to create a better learning experience (Ahmed & Elmubark, 2022;Jing & Yue, 2016;Minalti & Yeni, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The research outcomes were consistent with the previous study conducted by Fimala et al (2022), which showed an improvement of 86 percent in the students' learning results from the pre-test and post-test score data after employing a blended learning student worksheet using the Nearpod application in class. Ahmed and Elmubark (2022) conducted a study that demonstrated a significant difference in the mean scores of the pre-test and post-test, and the students participating in the study were delighted with the application of the Nearpod as an interactive media in the reading teaching-learning process. Pupah and Sholihah (2022) performed a study that proved the efficacy of Nearpod media that successfully supported the reading learning process in class for students because of its user-friendliness, and it enabled teachers to monitor students' progress during the teaching process.…”
Section: Discussionmentioning
confidence: 99%